2021
DOI: 10.3390/ijms22168913
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in Acute Kidney Injury and Clinical Applications

Abstract: Acute kidney injury (AKI)––the sudden loss of kidney function due to tissue damage and subsequent progression to chronic kidney disease––has high morbidity and mortality rates and is a serious worldwide clinical problem. Current AKI diagnosis, which relies on measuring serum creatinine levels and urine output, cannot sensitively and promptly report on the state of damage. To address the shortcomings of these traditional diagnosis tools, several molecular biomarkers have been developed to facilitate the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 155 publications
0
23
0
Order By: Relevance
“…Previous studies have highlighted the potential of MSC and MSC-derived exosomes in delaying and even reversing kidney disease [51,52] and for improving outcomes after kidney transplantation [53,54]. While these studies have shown immune-modulatory, anti-fibrotic, anti-apoptotic, pro-regenerative and pro-angiogenic properties of MSC or their derivatives, only a few reports are available regarding their potential effects on cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have highlighted the potential of MSC and MSC-derived exosomes in delaying and even reversing kidney disease [51,52] and for improving outcomes after kidney transplantation [53,54]. While these studies have shown immune-modulatory, anti-fibrotic, anti-apoptotic, pro-regenerative and pro-angiogenic properties of MSC or their derivatives, only a few reports are available regarding their potential effects on cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…The EV are classi ed as microvesicles that bud off the plasma membrane or exosomes that are secreted through the exocytic pathway. EV contain proteins speci c for their origin; therefore, changes in speci c EV's concentration during pathological processes can point towards affected cells or tissues (reviewed in [7]).…”
Section: Introductionmentioning
confidence: 99%
“…A delivery means specifically targeting the injured kidney cells, therefore, needs to be established. In this regard, extracellular vesicles (EVs) have emerged as a vehicle to achieve such renal injury-specific drug targeting, for these natural, membrane-bound nanoparticles can be engineered to transport desired drugs to the injury site with great precision and accuracy [3, 4].…”
mentioning
confidence: 99%
“…Notably, this so-called ischemic preconditioning (IPC) state can be transferred from a donor to a recipient, inducing remote IPC [5, 6]. Present in various body fluids such as blood, saliva, and urine, EVs are known to carry a specific set of cargo molecules that mirror the physiological and pathological status of the producing cells, eventually discharging the contents in EV-receiving cells [3]. Indeed, EVs derived from a donor of IPC are known to mount remote IPC in recipients, presumably through delivering a select set of cargos that reflect the IPC state, to assist injured kidney cells to recover [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation